2017
DOI: 10.1016/j.jid.2016.09.036
|View full text |Cite
|
Sign up to set email alerts
|

GPVI and Thromboxane Receptor on Platelets Promote Proinflammatory Macrophage Phenotypes during Cutaneous Inflammation

Abstract: Platelets are well known for their role in hemostasis but are also increasingly recognized for their supporting role in innate immune responses. Here, we studied the role of platelets in the development of peripheral inflammation and found that platelets colocalize with macrophages in the inflamed tissue outside of blood vessels in different animal models for cutaneous inflammation. Collagen-treatment of macrophages isolated from paws during zymosan-induced inflammation induced thromboxane synthesis through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 60 publications
1
56
0
Order By: Relevance
“…GPVI is a major collagen receptor that recognizes the quaternary structure of collagen, and activates platelets [60,61]. Platelet GPVI monomers shift from low affinity and signal transduction potential to multimers that gain high affinity collagen periodic structure [41,6265]. …”
Section: Platelet “First Response” Facilitated Clot/wound Biologymentioning
confidence: 99%
“…GPVI is a major collagen receptor that recognizes the quaternary structure of collagen, and activates platelets [60,61]. Platelet GPVI monomers shift from low affinity and signal transduction potential to multimers that gain high affinity collagen periodic structure [41,6265]. …”
Section: Platelet “First Response” Facilitated Clot/wound Biologymentioning
confidence: 99%
“…Most platelet functions and their interactions with other cell types are restricted to events taking place within the blood vessels. Recently, we found that platelets colocalize with macrophages outside of the blood vessels in several models for cutaneous inflammation and suppress the expression of anti-inflammatory markers and enhance the synthesis of proinflammatory mediators in the associated macrophages [5]. Monocytes in the bloodstream and macrophages in tissues play central roles in various immunological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, platelets store in granules a wide variety of signaling factors (e.g., mitogenic and angiogenic factors, chemokines (i.e., CXCL4), serotonin, histamine, nucleotides, and proteases), which are released upon platelet activation and have the potential to induce or to modulate proinflammatory responses of macrophages [21]. In addition, platelets are able to synthesize lipid mediators like thromboxane A2 (TXA2) [5, 22, 23] or PGE 2 [24, 25] upon activation. Furthermore, platelets have been shown to convert human peripheral blood circulating monocytes to IL-10-producing regulatory monocytes [26].…”
Section: Introductionmentioning
confidence: 99%
“…3D). Interestingly, this time frame corresponds with the appearance of monocyte-derived macrophages in the inflamed tissue during zymosan-induced inflammation [25,27].…”
Section: Mycbp2-deficiency Increases M2-marker Expression In Macrophagesmentioning
confidence: 93%